APLIKASI AKAD MURABAHAH PADA PRODUK KONSUMTIF DI BAITUL MAL WAT TAMWIL (BMT) AL-AMANAH CIAWI TASIKMALAYA - Denden S Hadi Wijaya; Us Us Surya Nopendi; Faisal Faisal (Prodi Hukum Ekonomi Syariah (Muamalah), 2020)
Sales-based Akad Murabahah is expected to be a system solution for the results that tend to be high risk. The issue arises more on disbursement of financing which leads to the authority to purchase goods buying and selling objects. The purpose of this research is to analyze the activities of the financial services developed and analyze the application of Akad Murabahah in BMT Al-Amanah Ciawi Tasikmalaya This research uses qualitative descriptive methods with the type of field research with inductive logic. Data collection is done by observation methods, interview methods, and documentation methods. The results of the research found that the financial services in BMT Al-Amanah Ciawi Tasikmalaya are: financial services and financial services financing. In the financing of consumptive products which in this case use the product of Ba'i al-Musawwamah which is an application of Akad Murabahah, there are some provisions regarding the desired product or needed. Because in general, all goods that are desired or required by the member can be facilitated financing by BMT Al-Amanah Ciawi Tasikmalaya. BMT Al-Amanah Ciawi Tasikmalaya implements the concept of trading contract (Murabahah) into 2 financing products namely Murabahah product which is a product of goods financing of business or productive and into the product of Ba'i Al-Musawwamah which is a financing product for consumptive goods